Pola Gangguan Muskuloskeletal Di Usia Produktif - Laksmita, Devinta Yulia; Mustiko, Prihantoro Larasati (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2024)
Musculoskeletal disorders (MSDs) have emerged as a significant public health concern that affects functional activities and decreases quality of life, especially in the productive age group. There remains a gap in the literature regarding the specific trends MSDs among the productive age group. This study aims to address the correlation between age and MSDs patterns in the productive age group. This study is a cross-sectional study with 136 respondents in the productive age groups (adolescents, adults, and pre-elderly). Identification of MSDs using the Nordic Body Map questionnaire and the correlation with age was tested using the Chi-Square test. A total of 98 (72.1%) respondents experienced MSDs with the most complaints in the adult age group (49%). Statistical showed a significant relationship (p <0.03) between age and MSDs with the low back, upper back, and hips being the most complained areas. This study shows a relationship between age and musculoskeletal disorders, further research should explore interventions to improve musculoskeletal health.